Peningkatan Hasil Belajar Siswa Kelas IX Melalui Penerapan Media Audio Visual di UPTD SMPN 5 Kec. Lareh Sago Halaban - Ilva Hendri; Zulfani Sesmiarni; Rodi Rodi; Zulfikri Zulfikri; Adeng Putra; Meyriza Hamda (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study aims to analyze the improvement of student learning outcomes in class IX through the application of audio-visual media. The method used in this research is Classroom Action Research, involving 19 students from class IX at UPTD SMPN 5, Lareh Sago Halaban. The results indicate that audio-visual media can enhance learning outcomes. In the pre-cycle, the average learning outcome of students was 65. In Cycle I, the average learning outcome increased to 73. After Cycle II, the average learning outcome rose to 78. Following Cycle III, the average learning outcome reached 82. The results of this study can serve as a recommendation for the use of media in teaching. It is hoped that this research will provide new insights into the selection of appropriate media for PAI (Islamic Education) learning. Keyword: , ,